2022
DOI: 10.3389/fpubh.2022.1039450
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of burnout during the prolonged pandemic in the Chinese zero-COVID context: COVID-19 burnout views scale

Abstract: Burnout is an important public health issue at times of the COVID-19 pandemic. Current measures which focus on work-based burnout have limitations in length and/or relevance. When stepping into the post-pandemic as a new Norm Era, the burnout scale for the general population is urgently needed to fill the gap. This study aimed to develop a COVID-19 Burnout Views Scale (COVID-19 BVS) to measure burnout views of the general public in a Chinese context and examine its psychometric properties. A multiphase approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Considering the importance of Burnout in the studies of Covid-19 (Lau et al, 2022 ), we expected this concept to be highlighted in the drawn networks; but despite including the relevant keyword in the search phase, this concept was not observed in the drawn networks. Considering that in drawing networks, citations are vitally important, it seems that documents related to Burnout have not received enough citations to be highlighted in the network.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the importance of Burnout in the studies of Covid-19 (Lau et al, 2022 ), we expected this concept to be highlighted in the drawn networks; but despite including the relevant keyword in the search phase, this concept was not observed in the drawn networks. Considering that in drawing networks, citations are vitally important, it seems that documents related to Burnout have not received enough citations to be highlighted in the network.…”
Section: Discussionmentioning
confidence: 99%
“…Second, 1 year after the pandemic, uncertainty around available resources and the evolution of the virus variants continued to challenge the health system ( 32 ). At this stage, strict restrictive measures were adopted in line with the zero-COVID policy ( 33 ). Health professionals experienced acute staffing shortages due to the huge efforts on the citywide test-trace-isolate, and following energy-exhausting protocols intended to keep everyone safe ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Partial lockdown and the factors that were associated with an increased level of depression, stress, and anxiety were being single, separated, or widowed, having a higher education level, a larger family size, loss of jobs, and being in contact with individuals (Le et al, 2020), and other study has found the household income loss due to the impact of COVID-19, People holding undergraduate degrees, working in other sectors rather than healthcare, and having definite-term contract had a higher likelihood of income reduction (Tran et al, 2020). Additionally, people's increasing intolerance for the adoption of health-protective measures for a prolonged time led to "pandemic burnout" (Moroń et al, 2021;Lau et al, 2022). It has been found that burnout caused by a pandemic can make people feel emotionally drained and affect people's every aspect of their life (WHO, 2022).…”
Section: Introductionmentioning
confidence: 97%
“…People who are stuck in pandemic burnout may lead to lower levels of motivation, feelings of helplessness, loneliness, hopelessness, depersonalization, and reduced personal achievement (Haktanir et al, 2022). Lau et al (2022) examined the psychometric properties of COVID-19 Burnout Views Scale (BVS) with a large Hong Kong sample and found the expected positive associations of COVID-19 BVS with the presence of chronic illnesses (Hayat et al, 2022), support for "living with the COVID" policy, i.e., by reducing the social distancing measures (Ligo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%